Analisis Kemampuan Guru dalam Menggunakan E-Learning sebagai Media Pembelajaran di Era Digital - Adam Hasyim; Nurul Awaliah Hayati (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2023)
The teacher's efforts to achieve the success of the goal in learning by using the media to facilitate the delivery of planned teaching material, for example, internet media, or in other terms-learning is the answer to this need. Important abilities must be possessed by teachers in the modern age and the digital era of using e-learning is a must. This study aims to determine the extent to which the teacher's ability to use e-learning as a learning medium in the digital era and also the obstacles in Fatahillah Middle School, Tambakdahan District, Subang Regency. While the researchers used a qualitative approach to the type of descriptive research. Then data collection techniques using observation, interviews, and documentation. The results of the research found that teachers use e-learning as a learning medium in the digital era at Fatahillah Middle School, Tambakdahan Subdistrict, Subang Regency, it is already skilled and adequate, moreover, it is supported by good infrastructure to make learning use of e-learning as a learning medium runs smoothly as expected. It's just the intensity of the use of e-learning seldom done. In addition, teachers do not take advantage of the wealth of learning support application features-learning.